Opiate use inhibits TLR9 signaling pathway in vivo: possible role in pathogenesis of HIV-1 infection. Issue 1 (December 2017) - Liao, Yanyan; Jiang, Junjun; Liang, Bingyu; Wei, Fumei; Huang, Jiegang; Pan, Peijiang; Su, Jinming; Zhou, Bo; Zang, Ning; Ye, Li; Liang, Hao
Abstract The molecular mechanism of opiate use promoting HIV-1 infection is not fully understood. TLR9 is expressed in many immune cells, including monocytes, macrophages, which can recognize viruses and viral products and consequently induce the production of antiviral factors and initiate immune responses. Previous studies have shown that chronic viral infections can overcome and impair TLR9 pathway. We aimed to explore whether opiate use enhances HIV infection through inhibition of TLR9 pathway via a population-based study. A total of 200 subjects were enrolled and divided into four groups as follows: Opiate+ HIV+ (50), Opiate− HIV+ (50), Opiate+ HIV− (50), and healthy control (Opiate− HIV−, 50). All HIV-infected subjects did not receive antiretroviral therapy while they were enrolled in the study. The results showed that opiate use was associated with higher viral load and lower CD4+ T cell count. Opiate use alone led to lower expression of TLR9, IRF7, and IFN-α at the protein level in PBMCs. Combined with HIV-1 infection, opiate use resulted in lower expression of MyD88, ISG56, and MxA. In addition, morphine treatment promoted HIV-1 replication in macrophages via inhibition of TLR9 pathway. Our data reveal that opiate use plays a cofactor role in pathogenesis of HIV-1 infection through inhibition of TLR9 pathway.